2017
DOI: 10.1016/j.virol.2017.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Infected T98G glioblastoma cells support human cytomegalovirus reactivation from latency

Abstract: T98G cells have been shown to support long-term human cytomegalovirus (HCMV) genome maintenance without infectious virus release. However, it remains unclear whether these viral genomes could be reactivated. To address this question, a recombinant HCMV (rHCMV) containing a GFP gene was used to infect T98G cells, and the infected cells absent of infectious virus production were designated T98G-LrV. Upon dibutyryl cAMP plus IBMX (cAMP/IBMX) treatment, a serial of phenomena were observed, including GFP signal inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…Human cytomegalovirus (HCMV) components have been found to be present in a large proportion of glioblastoma (GBM) (Cobbs et al, 2002). HCMV establishes latency in T98G glioblastoma cells and latent HCMV can be reactivated (Cheng et al, 2017). It was also reported that HCMV potentially induces a functional mesenchymal-to-epithelial (MET) transition without affecting their viability in transformed breast carcinoma and glioma stem cells, which might encourage tumor colonization (Oberstein and Shenk 2017).…”
mentioning
confidence: 99%
“…Human cytomegalovirus (HCMV) components have been found to be present in a large proportion of glioblastoma (GBM) (Cobbs et al, 2002). HCMV establishes latency in T98G glioblastoma cells and latent HCMV can be reactivated (Cheng et al, 2017). It was also reported that HCMV potentially induces a functional mesenchymal-to-epithelial (MET) transition without affecting their viability in transformed breast carcinoma and glioma stem cells, which might encourage tumor colonization (Oberstein and Shenk 2017).…”
mentioning
confidence: 99%
“…In this regard we decided to verify their expression in a GBM cell line. Previous studies have shown that established GBM cells, with different degrees of differentiation, exhibit different levels of permissiveness to HCMV infection and replication [ 45 51 ]. In these cells, the kinetics of protein expression is delayed, and low numbers of progeny viruses are produced [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to choose proper cell types and strains to establish a cell model for cross-species infection of HCMV. In human, primary fibroblasts with skin or lung origin are mostly used to study in vitro HCMV infection because it is one of the main target cell types, easy to culture, permissive for all strains, and supports production of high titer of cell-free virus [20]. Towne strain, one of the mostly used laboratory strain, has been reported to be permissive for HCMV infection of CF.…”
Section: Discussionmentioning
confidence: 99%